Glial reactivity in dogs with visceral leishmaniasis: correlation with T lymphocyte infiltration and with cerebrospinal fluid anti-Leishmania antibody titres - Melo, Guilherme D.; Machado, Gisele Fabrino [UNESP] (Springer, 2011)
Visceral leishmaniasis is a multisystemic zoonotic disease that can manifest with several symptoms, including neurological disorders. Because glial cells are extensively associated with the immune response within the brain, we evaluated the morphology of astrocytes and microglia of dogs naturally infected with Leishmania chagasi. We used immunohistochemical and lectin-histochemical techniques for morphological analyses and we also examined the glial correlation with lymphocyte infiltration of the brain and with the presence of anti-Leishmania antibodies within the cerebrospinal fluid of the dogs. Although we did not detect a shared morphological pattern in the astrocytes or microglia in the brain tissue, these cells were more intensely labelled in infected dogs than in the control group. The density of microglia was increased in the ependymal/subependymal area, thus demonstrating a strong correlation with the presence of T lymphocytes and with cerebrospinal fluid antibody titres. Thus, our results indicate a pro-inflammatory state in the brains of dogs naturally infected with L. chagasi and strongly suggest that microglia and astrocytes are involved in the pathogenesis of the neurological disorders of visceral leishmaniasis in dogs.
Keywords: Astrocyte; Central nervous system; Inflammation; Microglia; Canine; Leishmania chagasi